Influence of Reading Interest and Vocabulary Mastery on Students' Reading Comprehension Ability - Retno Wulan; Farida Nugrahani; Suwarto (Tarbiyah Departement collaboration with AMCA, 2023)
Reading interest and vocabulary mastery can affect students' reading comprehension skills. The level of reading comprehension ability in the high class has yet to show satisfactory results. The low interest in reading students is due to a lack of awareness of students to read; besides that, students' vocabulary mastery still needs to improve due to a lack of student's ability to interpret words. This research is a correlational study with a quantitative approach. The population in this study were fourth-grade students at SDN Bendung 1 Semin. The sampling technique uses a saturated sample where all students are the sample. Data collection techniques were used in this study using questionnaires and tests. The instrument test was carried out by testing the validity and reliability tests. The data analysis used is descriptive and statistical. The results showed that: (1) there was a negative and not significant effect of reading interest on reading comprehension ability with a value of tcount = -0.129 with a significance of 0.900 > 0.05 with a contribution of 2.4%, (2) there was a positive effect but not significant vocabulary mastery on reading comprehension ability with a value of tcount = 0.671 with a significance of 0.515 > 0.05 with a contribution of 18.8%, (3) there is a positive and significant effect of interest in reading and vocabulary mastery on reading comprehension ability devalued by Fcount of 0.299 with a significance value of 0.799 > 0.05 with a contribution of 3.7%. Â